A millennium-long 'Blue Ring' chronology from the Spanish Pyrenees reveals severe ephemeral summer cooling after volcanic eruptions. (27th November 2020) - Piermattei, Alma; Crivellaro, Alan; Krusic, Paul J; Esper, Jan; Vítek, Petr; Oppenheimer, Clive; Felhofer, Martin; Gierlinger, Notburga; Reinig, Frederick; Urban, Otmar; Verstege, Anne; Lobo, Hannah; et al.
Abstract: ' Blue Rings' (BRs) are distinct wood anatomical anomalies recently discovered in several tree species from different sites. While it is evident that they are associated with a cooling-induced lack of cell wall lignification, BRs have yet to be evaluated systematically in paleoclimate studies. Here, we present a continuous wood anatomical assessment of 31 living and relict pine samples from a high-elevation site in the central Spanish Pyrenees that span the period 1150–2017 CE at annual resolution. While most BR years coincide with cold summer temperatures and many BRs follow large volcanic eruptions, some were formed during overall warm summers. We also see a differential response between eruptions: the Samalas eruption is followed by 80% BRs in 1258, but only a modest signal is evident after the 1815 Tambora eruption, and there are no wood anatomical effects of the Laki eruption in 1783–1784. Apparently linked to a cluster of tropical eruptions in 1695 and 1696 CE, 85% BRs occurred in 1698. This new wood anatomical evidence is corroborated by the record of sulphur deposition in polar ice cores, and corresponds with catastrophic famine and unprecedented mortality in Scotland. The extremely rare occurrence of consecutive BRs in 1345 and 1346 marks the onset and spread of the Black Death, Europe's most devastating plague pandemic. In their ability to capture severe ephemeral cold spells, as short as several days or weeks, BR chronologies can help to investigate and understand the impacts of volcanism on climate and society.